Portrait of a woman, formerly identified as Claude of France label... - Corneille de Lyon (Wikimedia Commons)
Oeuvre issue de Wikimedia Commons pour la demo du fonds documentaire. Titre: Portrait of a woman, formerly identified as Claude of France label....
Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons